Advanced methods for complex network analysis - Meghanathan, Natarajan 1977- (Advances in wireless technologies and telecommunication (AWTT) book series, 2016)
This book features the latest research on the algorithms and analysis measures being employed in the field of network science, highlighting the application of graph models, advanced computation, and analytical procedures